DRIVING FACTORS AND BARRIERS OF YOUTH PARTICIPATION IN VILLAGE DEVELOPMENT: A CASE STUDY OF TOLONDADU I VILLAGE - Arif Chandra Kirana; Imam Mashudi; Ely Ibrahim (LP2M Universitas Bina Mandiri Gorontalo, 2026)
The strategic involvement of young people is essential for sustainable rural development, yet their participation is often constrained by various structural and personal challenges. This study aims to analyze: (1) the factors driving youth participation in local governance, (2) the barriers hindering their involvement, and (3) the collaborative strategies developed by the village government and youth organizations to promote inclusive rural development. The research was conducted in Tolondadu I Village, Bolaang Uki District, South Bolaang Mongondow Regency, using a qualitative approach within a post-positivist paradigm. Data were collected through observation, documentation, and semi-structured in-depth interviews with three key informants selected through purposive sampling: the Village Head, Village Secretary, and Chairman of Karang Taruna. Data were analyzed using a qualitative descriptive method and validated through source triangulation and prolonged observation. The findings reveal that institutional inclusion serves as the main driving factor for youth participation. Democratic forums, such as Village Deliberation Meetings (Musyawarah Desa), provide opportunities for young people to actively contribute to local decision-making processes. However, youth participation remains limited due to structural barriers, including migration for education and employment, as well as personal factors such as career-oriented individualism and financial pragmatism. To address these challenges, stronger collaboration between the village government and Karang Taruna is required. The village government can support youth engagement through policies and economic programs, while Karang Taruna can utilize its social networks to align development initiatives with the aspirations and needs of young people.